Armenia Country Economic Update, Summer 2018 : An Opportunity to Unlock Armenia's Potential - World Bank Group (World Bank, Washington, DC, 2018)
This edition of Armenia's Country Economic Update is part of a semi-annual series designed to monitor socio-economic developments in Armenia. This edition covers the developments in 2017 and first few months of 2018.